Notes on four species of Russula subgenus Heterophyllidiae (Russulaceae, Russulales) from southern China - Han, Yun-Xiao; Liang, Zhi-Qun; Zeng, Nian-Kai (Frontiers in Microbiology, 2023)
Heterophyllidiae, one of the main subgenus of Russula (Russulaceae, Russulales), is both ecologically and economically important. Although many studies have focused on subgenus Heterophyllidiae in China, the diversity, taxonomy and molecular phylogeny still remained incompletely understood. In the present study, two new species: R. discoidea and R. niveopicta, and two known taxa: R. xanthovirens and R. subatropurpurea were described based on morphology and molecular phylogenetic analyses of ITS and 28S DNA sequences with new collections of subgenus Heterophyllidiae from southern China. Both morphological and phylogenetic analysis consistently confirmed that R. niveopicta and R. xanthovirens belong to subsect. Virescentinae, R. discoidea and R. subatropurpurea come under subsect. Heterophyllae, and R. prasina is synonymized with R. xanthovirens.